Research Papers:Shirley as Elegy. (January 2015) - Stoneman, Patsy
Abstract : Charlotte Brontë's Shirley has never been a popular novel, partly because it seems to lack focus, shifting between a general concern with the condition of England and the particular situation of its unmarried women. The fact that all three of Charlotte's remaining siblings died during its composition has been cited only as mitigating its evident faults. This essay, however, takes seriously Charlotte's puzzling declaration that the character of Shirley was her effort 'to depict [...] what Emily Brontë would have been, had she been placed in health and prosperity', arguing that aspects of the novel can be read in terms of traditional elegy. With reference to Freud's essay, 'Mourning and Melancholia', and Derrida's book, The Work of Mourning, the essay concludes that Charlotte's effort at elegizing her sister is most successful not in the passages describing Shirley's near-apotheosis, but in the novel's pervasively elegiac descriptions of the natural world.